The urgency of introducing balanced nutrition in early childhood to prevent stunting - Nurjanah, Riska Siti; Safitri, Wulan; Somantri, Wendra Riyadi; Ikrimah, Awalia Latifa Mayda (Universitas Pendidikan Indonesia, 2023)
Maternal and child mortality has increased due to stunting, triggered by the unbalanced nutritional intake of food consumed. 1000 HPK is essential for food needs, such as consuming vegetables, fruit, protein, carbohydrates, and fats. The method used to overcome this problem is counseling on nutritious intake to avoid the dangers of stunting for children. The results of the service activities are known that children in some areas of Margaasih Village already know and are aware of nutritious food intake. Nutritious food intake needs to be consumed every day by children to avoid stunting problems that cause them to have low IQ and developmental disorders until they grow up. However, the counseling activities we do through the method of coloring pictures of the contents of my plate need to be complemented with natural vegetables or fruits so that children better understand the images we provide. This counseling is expected to instill good habits for children to consume food with balanced nutrition.